2006
DOI: 10.1038/sj.cdd.4401898
|View full text |Cite
|
Sign up to set email alerts
|

Aplidin® induces JNK-dependent apoptosis in human breast cancer cells via alteration of glutathione homeostasis, Rac1 GTPase activation, and MKP-1 phosphatase downregulation

Abstract: Aplidins is an antitumor agent in phase II clinical trials that induces apoptosis through the sustained activation of Jun N-terminal kinase (JNK). We report that Aplidin s alters glutathione homeostasis increasing the ratio of oxidized to reduced forms (GSSG/GSH). Aplidin s generates reactive oxygen species and disrupts the mitochondrial membrane potential. Exogenous GSH inhibits these effects and also JNK activation and cell death. We found two mechanisms by which Aplidin s activates JNK: rapid activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 45 publications
3
59
0
Order By: Relevance
“…The sustained activation and phosporylation of c-Jun N-terminal kinase (JNK) by reactive oxygen species (ROS) is recognised as one of the crucial mechanisms in the effects of Aplidin on breast cancer cells (Garcia-Fernandez et al, 2002;Cuadrado et al, 2004;GonzalezSantiago et al, 2006;Suarez et al, 2006). This ROS induction was found to be caused by an alteration in the glutathione homeostasis and by a rapid activation of the small GTP-binding protein Rac (Cuadrado et al, 2003;Gonzalez-Santiago et al, 2006). Next to phosphorylation of JNK, Aplidin also causes cleavage of Bid, a proapoptotic Bcl-2-family member that connects the Fas/CD95 cell death receptor (DR) to the mitochondrial apoptotic pathway, in human leukaemic cell lines (Gajate et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The sustained activation and phosporylation of c-Jun N-terminal kinase (JNK) by reactive oxygen species (ROS) is recognised as one of the crucial mechanisms in the effects of Aplidin on breast cancer cells (Garcia-Fernandez et al, 2002;Cuadrado et al, 2004;GonzalezSantiago et al, 2006;Suarez et al, 2006). This ROS induction was found to be caused by an alteration in the glutathione homeostasis and by a rapid activation of the small GTP-binding protein Rac (Cuadrado et al, 2003;Gonzalez-Santiago et al, 2006). Next to phosphorylation of JNK, Aplidin also causes cleavage of Bid, a proapoptotic Bcl-2-family member that connects the Fas/CD95 cell death receptor (DR) to the mitochondrial apoptotic pathway, in human leukaemic cell lines (Gajate et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the cell system, Aplidin either induces a very rapid apoptotic death without previous cell cycle arrest or causes a block in G 1 and/or a delay in the progression from S to G 2 phases of the cell cycle (11,12). Further studies have shown that Aplidin induces apoptosis by altering glutathione homeostasis, thereby increasing the levels of reactive oxygen species and inducing Rac1 GTPase activation and MKP-1 phosphatase down-regulation (14). As part of its antitumoral action in leukemic cells, Aplidin has been shown to reduce the secretion of vascular endothelial growth factor and to down-regulate its receptor, vascular endothelial growth factor receptor-1 (flt-1; refs.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 278 plitidepsin cycles were administered during the study, with a median of 4 cycles per patient (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Before the amendment, 23 patients received a median of 4 cycles of single-agent plitidepsin (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…Plitidepsin-induced oxidative stress leads to increased levels of cell membrane phospholipid as well as DNA oxidation (8), decreased intracellular levels of glutathione, and sustained activation of the Rac1-JNK pathway that ultimately leads to caspase-dependent apoptosis (9)(10)(11). In addition, plitidepsin has shown antiangiogenic activity in several preclinical models through inhibition of the expression of several angiogenic genes, including the vascular endothelial growth factor (VEGF) and its receptor (VEGFR-1; refs.…”
mentioning
confidence: 99%